À la recherche de l'identité dans l'oeuvre de Frédérick Tristan - Kubínyiová, Petra; Kyloušek, Petr, 1952-; Masarykova univerzita. Ústav románských jazyků a literatur (2007)
V diplomové práci À la recherche de l'identité dans l'oeuvre de Frédérick Tristan se zabýváme tématem hledání identity v díle Frederika Tristana. Téma identity je všudypřítomným momentem autorovy tvorby a představuje její výchozí bod. To je důvod, proč se tato otázka stala hlavním předmětem našeho zkoumání, jež se zaměřuje na hledání identity Tristanovými hrdiny a na proces jejich proměny.
In the master thesis A la recherche de lidentité dans loeuvre de Frédérick Tristan we are engaged in the theme of searching for identity in Frédérick Tristans literature production. This theme is omnipresent moment of authors writings and represent the point of departure for all his work. Thats the reason why the question of identity has become the main topic of our analysis which is focused on searching for identity by Tristans main characters and on the process of their transformation.
Vedoucí práce: Petr Kyloušek
Diplomová práce (Mgr.)--Masarykova univerzita, Filozofická fakulta, 2007
Keywords: Tristan, Frédérick, -- 1931-2022; 20.-21. století; francouzská literatura -- 20.-21. století; identita; French literature -- 20th-21st centuries; identity; diplomové práce; master's theses